An optimization approach to the scale of port cold-chain dedicated terminals considering uncertainties. Issue 11 (2nd November 2022) - Ma, Qianli; Ma, Baiyu; He, Ying; Sun, Weimeng
Abstract : As an important node of the international cold-chain logistics system, the special terminal for refrigerated ships is the core facility for cargo loading and unloading. To minimize the sum of construction costs and operating costs of dedicated cold-chain terminals, a stochastic programming model is established considering uncertainty of the type and time of arrival of refrigerated vessels and special requirements for cargo handling and storage, and the simulation optimization method based on tabu search is used to determine the optimal scale of cold-chain terminals. A case study on the port cold-chain system of an offshore fishery base is then presented to investigate the specific influence of uncertainties on the scale of cold-chain terminals. This provides a reference for scientific planning of cold-chain facilities and improving the efficiency of cold-chain systems in the sea–land exchange node.